Answer:
Step-by-step explanation:
Givens
x + y = 2
x - y = 6
Solution
Just add the two equations together. The y's will drop out.
x + y = 2
<u>x - y = 6 </u> Add
2x = 8 Divide by 2
2x/2 = 8/2 Combine
x = 4 Substitute x = 4 into the top equation
x + y = 2
4 + y = 2 Subtract 4 from both sides
4-4+y=2-4 Combine
y = - 2
Answer
x = 4
y = -2
Answer:
9.004, 9.04, 9.2, 9.2032
Step-by-step explanation:
For this case the volume of the box is given by:
V = l * w * h
Where,
V = 24 feet ^ 3
Substituting values we have:
24 = l * w * h
Clearing the value of h we have:
h = 24 / (l * w)
Answer:
The height in terms of the other sides is:
h = 24 / (l * w)
Answer:
99.06%
Step-by-step explanation:
100.00% - 0.94% = 99.06%
The inverse demand function of the given demand function is <u>p = 50 - q/2</u>.
A graph that depicts the relationship between a product's price and demand is called a demand curve. On a demand graph, the horizontal axis represents the amount desired, while the vertical axis represents the product's price.
The price is a function of the quantity required when there is an inverse demand curve. The inverse of a demand curve indicates that variations in the amount required cause changes in price levels. The formula for calculating the demand curve for a product yields the graph of an inverse demand curve.
Given demand function: q = 100 - 2p.
To find the inverse demand function, we find the inverse of the equation, by isolating p, to get:
q = 100 - 2p,
or, 2p = 100 - q,
or, p = 100/2 - q/2,
or, p = 50 - q/2.
Thus, the inverse demand function of the given demand function is <u>p = 50 - q/2</u>.
Learn more about inverse functions at
brainly.com/question/3831584
#SPJ4